The effect of social capital on individual happiness in Indonesia - Ni Putu Wiwin Setyari; Putu Ayu Pramitha Purwanti; Ida Ayu Nyoman Saskara; I Komang Gde Bendesa (SIMULACRA: JURNAL SOSIOLOGI, 2022)
This study examines how social capital affects the well-being of individuals in Indonesia. Happiness determinants use several aspects of social capital at the same time: trust, information channels, civic participation, especially political participation. In addition, this estimation also takes into account other socio-demographic factors. The researchers found that trust, information channels, and political participation have a significant impact on the well-being of Indonesian. Individual trust and sociable gatherings to leave a child to a close-neighbor within a few hours have a positive effect on the individual’s well-being. By using IFLS data, a logistic model is used to test whether some indicators of social capital affect individual’s well-being. A positive correlation between social capital and happiness may suggest that public policies toward increasing social capital both at the individual and aggregate level may have complementary effects on raising individual’s well-being. It is important to support the government`s efforts in improving the community’s happiness which in turn can encourage development policies` effectiveness.